Leadership Style and Resilience: Mediating Role of Learning Culture in Nepalese Organizations - Sharma , Rajiv; Prajapati , Bikram; Khanal , Krishna (Journal of Innovation in Academia, 2025)
Organizational resilience is essential for businesses, especially in uncertain environments like Nepal. However, there is limited understanding of how different leadership styles influence resilience and the mediating role of organizational learning culture in this relationship. This study addresses this gap by examining the relationship between transformational and transactional leadership styles, organizational resilience, and the mediating effect of organizational learning culture within the Nepali manufacturing and service industries. A cross-sectional survey was conducted among 340 employees across 40 diverse Nepalese organizations. The data were analyzed using Structural Equation Modeling (SEM) to test the hypothesized relationships. The findings revealed that neither transformational nor transactional leadership styles had a direct significant impact on organizational resilience. However, organizational learning culture fully mediated the relationship between both leadership styles and resilience. This highlights the importance of cultivating a learning-oriented culture to strengthen organizational resilience, regardless of leadership style.